Government Promotion of Corporate Social Responsibility: Evidence from the EU Eco‐Management and Audit Scheme. Issue 1 (18th December 2018) - Whitford, Andrew B.; Provost, Colin
Abstract: Governments play an active role in promoting corporate social responsibility and specifically environmental management system (EMS) programs, but few studies have examined the impact of such support on the decision of businesses to adopt EMS programs. We ask two questions in this paper: how does government support for EMS programs affect adoption of such programs? Second, what effect does this government support have on the pace of adoption of such programs? The answer to the first question can reveal how effective government programs are in boosting membership in EMS programs. The answer to the second reveals to what extent businesses within EU member states are converging upon particular EMS standards. We examine these questions in the context of the European Union's Eco‐Management and Audit Scheme (EMAS), 2010–2014. There is significant variation in government support of EMAS across the EU and at the same time, EMAS competes for business attention with the more established ISO 14001. Our quantitative and qualitative analyses therefore reveal the effectiveness of government programs in boosting adoption, but also to the extent to which such programs cause convergence upon EMAS in the face of a competing standard such as ISO 14001.